Lipocalin-2 Is a Key Regulator of Neuroinflammation in Secondary Traumatic and Ischemic Brain Injury - Kim, Jae-Hong; Kang, Ri Jin; Hyeon, Seung Jae; Ryu, Hoon; Joo, Hyejin; Bu, Youngmin; Kim, Jong-Heon; Suk, Kyoungho (Elsevier BV, 2023)
Reactive glial cells are hallmarks of brain injury. However, whether these cells contribute to secondary inflammatory pathology and neurological deficits remains poorly understood. Lipocalin-2 (LCN2) has inflammatory and neurotoxic effects in various disease models; however, its pathogenic role in traumatic brain injury remains unknown. The aim of the present study was to investigate the expression of LCN2 and its role in neuroinflammation following brain injury. LCN2 expression was high in the mouse brain after controlled cortical impact (CCI) and photothrombotic stroke (PTS) injury. Brain levels of LCN2 mRNA and protein were also significantly higher in patients with chronic traumatic encephalopathy (CTE) than in normal subjects. RT-PCR and immunofluorescence analyses revealed that astrocytes were the major cellular source of LCN2 in the injured brain. Lcn2 deficiency or intracisternal injection of an LCN2 neutralizing antibody reduced CCI- and PTS-induced brain lesions, behavioral deficits, and neuroinflammation. Mechanistically, in cultured glial cells, recombinant LCN2 protein enhanced scratch injury-induced proinflammatory cytokine gene expression and inhibited Gdnf gene expression, whereas Lcn2 deficiency exerted opposite effects. Together, our results from CTE patients, rodent brain injury models, and cultured glial cells suggest that LCN2 mediates secondary damage response to traumatic and ischemic brain injury by promoting neuroinflammation and suppressing the expression of neurotropic factors.